Aplasia and agenesis of the frontal sinus in individual of southern region in Saudi Arabia - Shamakhi, Radeif; Mubaraki, Musleh; Dighriri, Ramzi; Almarir, Azza; Alyahya, Alaa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The aim of this study was to demonstrate the prevalence of anatomic variations of frontal sinus in people of southern region in Saudi Arabia. Methods: This study used a retrospective radiological design to analyze computed tomography scans of 117 patients aged between 18 and 80 years of southern region in Saudi Arabia were used in this study. Patients with altered anatomy (iatrogenic or pathological) were excluded, CT scans were analyzed to demonstrate the incidence of anatomic variations of frontal sinus in people of southern region in Saudi Arabia. Results: The study included 117 patients, 75 of whom were males (64%) and 42 of whom were females (36%) with ages ranging from 18 to 80 years. The prevalence of bilateral frontal sinus aplasia is 5.9 % and 3.4% is in the unilateral frontal sinus. Conclusions: These figures on frontal sinus aplasia are critical in convincing surgeons to perform a preoperative CT scan of the paranasal sinuses and concentrate on the appearance of frontal sinuses on CT images to avoid unwanted complications during sinus surgeries.